Historical dictionary of Chinese intelligence - Smith, I. C. (Ivian C.) (Scarecrow Press, 2012)
"The Historical Dictionary of Chinese Intelligence covers the history of Chinese Intelligence from 400 B.C. to modern times. This is done through a chronology, an introductory essay, an extensive bibliography, and an index. The dictionary section has over 400 cross-referenced entries on the agencies and agents, the operations and equipment, the tradecraft and jargon, and many of the countries involved. This book is an excellent access point for students, researchers, and anyone wanting to know more about Chinese Intelligence"-- Provided by publisher.
Keywords: Intelligence service -- China -- History -- Dictionaries.; Military intelligence -- China -- History -- Dictionaries.; POLITICAL SCIENCE / Political Freedom & Security / Intelligence.; HISTORY / Asia / China.; POLITICAL SCIENCE / Reference.; REFERENCE / Dictionaries.; Intelligence service; Military intelligence; China; Dictionaries; History